Non nucleoside reverse transcriptase inhibitors, molecular docking studies and antitubercular activity of thiazolidin-4-one derivatives - Chitre, Trupti S.; Patil, Shital M.; Sujalegaonkar, Anagha G.; Asgaonkar, Kalyani D.; Khedkar, Vijay M.; Garud, Dinesh R.; Jha, Prakash C.; Gaikwad, Sharddha Y.; Kulkarni, Smita; Choudhari, Amit; Sarkar, Dhiman (Current Computer-Aided Drug Design, 2019)
Background: Management of Co-existence of Acquired immunodeficiency syndrome and Tuberculosis has become a global challenge due to the emergence of resistant strains and pill burden. Objective: Hence the aim of the present work was to design and evaluate compounds for their dual activity on HIV-1 and Tuberculosis (TB). Methods: A series of seven, novel Thiazolidin-4-one derivatives were synthesized and evaluated for their anti-HIV and anti-tubercular activity along with Molecular docking studies. All the seven compounds displayed promising activity against the replication of HIV-1 in cell-based assays. The four most active compounds were further evaluated against X4 tropic HIV-1(UG)(070) and R5 tropic HIV-1(vB59) primary isolates. The binding affinity of all the designed compounds for HIV-RT and Mycobacterium tuberculosis Enol Reductase (MTB InhA) was gauged by molecular docking studies which revealed crucial thermodynamic interactions governing their binding. Results: The CC50 values for the test compounds were in the range of, 15.08-34.9 mu g/ml, while the IC50 values were in the range of 16.1-27.13(UG(070); X4) and 12.03-23.64 (VB59; R5) mu g/ml. The control drug Nevirapine (NVP) exhibited CC50 value of 77.13 mu g/ml and IC50 value of 0.03 mu g/ml. Amongst all these compounds, compound number 3 showed significant activity with a TI value of 2.167 and 2.678 against the HIV-1 X4 and the R5 tropic virus respectively. In anti-mycobacterial screening, the compounds proved effective in inhibiting the growth of both log phase and starved MTB cultures. Conclusion: Compound 3 has been found to be active against HIV-1 as well as MTB.
Keywords: anti-HIV-1 activity; Antitubercular activity; human immunodeficiency virus-1; Molecular docking; Non nucleoside reverse transcriptase; thiazolidin-4-ones